Elementos da base de conhecimentos e processos de raciocínio pedagógico de uma mentora iniciante de professoras dos anos iniciais do ensino fundamental em início de carreira: um estudo de caso - Alarcon, Jéssica Francine Ferreira da Silva (Universidade Federal de São Carlos, 2024)
This research is related to the Hybrid Mentoring Program (HMP) of the Federal University of São Carlos, which lasted between 2017 and 2020. Coordinated by professors from the research group: Teacher Training and Other Educational Agents, at Federal University of São Carlos, it was funded by the São Paulo Research Foundation. Mentoring is an initiative where experienced teachers, known as mentors, provide guidance and advice to novice teachers to assist them with the demands of the early stages of their careers. The aim is to promote autonomy and support in the professional development of teachers. It prioritizes trust and mutual support between experienced and novice teachers and fosters situations of socialization in the school culture, based on the needs experienced in the context. In this research, the objective is to understand how the elements of the knowledge base are configured, understood as the set of knowledge necessary to teach, and the pedagogical reasoning process, which portrays the thinking and how knowledge is built during the process of teaching and learning, of an experienced teacher who worked at HMP as a beginning mentor for a beginning teacher who works in the early years of Elementary School, are configured. It is understood, from this perspective, that the process of pedagogical reasoning, although it is articulated with the knowledge base, is 'greater' in the movement of constitution, mobilization and connection of knowledge. In order to do this, a descriptive analytical-interpretative analysis is proposed, having as a data source: (a) narratives written in the Virtual Learning Environment (VLE) by the mentor; (b) online interactions records between mentor and beginning teacher and (c) interview (oral narrative). The results of this study indicate that the construction of the mentor's knowledge base involved: i) the environment of her work at HMP, with online interaction with the novice teacher, mostly asynchronous, but with training to be a hybrid mentor (with online and face to-face activities); ii) the context in which the beginner operates, her planning and her characteristics and needs, as well as those of her students; iii) the educational and social scenario – before and during the pandemic. And, in view of this, it encompassed: a) initial and continuing training to be a mentor; b) support from the Program's training team; c) online interaction with the beginner and a greater difficulty in building bonds of trust; d) the need for objective writing, but with strategies to establish greater proximity to the beginning teacher e) work methodology that would enable the verification of the beginner's demands and list the priorities; f) means to lead beginning teacher to reflect on its practice and, thus, obtain more information about their work context and performance; g) elaboration of proposals that would meet the needs of the beginner and her students; h) constant verification of the understanding of beginning teacher and its performance as a mentor; i) re-elaboration of proposals based on the understanding of the beginning teacher's understanding; j) evaluation and reflection on the new knowledge of beginning teacher and the development of autonomy in its teaching practice. And this included the scenario before and during the pandemic, in which strategies needed to establish new considerations and ways of acting. In other words, the process of reflection, or pedagogical reasoning, permeated the entire process of building the mentor's knowledge base and involved the context of action. In this sense, the pedagogical reasoning process included the choices, decision-making and actions of the mentor when advising the beginning teacher.
Elements of the knowledge base and pedagogical reasoning processes of a beginner mentor of beginning teachers in the elementary school: a case study
Keywords: Desenvolvimento profissional docente; Aprendizagem da docência; Mentoria; Ensino fundamental; Teacher professional development; Teaching learning; Mentoring; Elementary school; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM